PENINGKATAN PEMBELAJARAN BAHASA ARAB MELALUI INDEKS KATA DAN FRASA DALAM BAHAN AJAR DI MADRASAH IBTIDAIYAH NON PESANTREN - Baroroh, R. Umi; Shodik, M. Jakfar; Fransiska, Tony (Arabi : Journal of Arabic Studies, 2016)
The factor of failure in Arabic language learning in Indonesia is the lack of activities in language learning. One of language learning activities is identifying meaning or word meaning and phrase in dictionary. However, word and phrase index developed based on teaching materials at madrasah non-pesantren was not developed yet. Therefore, Research and Development is needed to apply. After having collected the word and phrase index that were collected from teaching materials of Arabic language at MI non-pesantren in Indonesia, then it was tested at MIN Malang. The result showed that: there was a development in Arabic language learning through word and phrase index; that was students’ competence to identify meaning and collaboration in understanding text and context in a sentence. After having applied the experiment, students’ average score increased from 52 with 19 failed students to 81,26 with 5 failed students.DOI: 10.24865/ajas.v1i2.6